Low-Cost Fabrication of a Rear-Projection Display Assembly Using Consumer-Grade Components for Pseudo-Holographic Applications - Kasmir Syariati; Citra Suardi; Reinaldo Lewis Lordianto; Andrey Hartawan Suwardi; Muhammad Aditya Ridwan; Enrico Kevin Ariantho; Javin Erasmus Clementino (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2025)
Rear-projection surfaces are integral to pseudo-holographic and immersive display systems, yet commercial solutions often demand expensive materials and precision hardware. This paper presents the design, fabrication, and preliminary evaluation of a low-cost rear-projection display assembly constructed from consumer-grade components. A transparent rear-projection film of unknown specification was mounted onto a custom 3D-printed frame and affixed to a flat acrylic sheet to form a projection screen. Assembly relied on readily available materials and hobbyist fabrication techniques. Qualitative projection tests using a standard classroom projector demonstrate that the DIY screen produces clear images with wide viewing angles in dark environments, suitable for pseudo-holographic effects. Under moderate ambient light, the image remains visible with slight contrast loss and minimal hot-spotting. The entire assembly was built at a fraction of the cost of commercial rear-projection screens. These results suggest that the proposed workflow can enable affordable, functional rear-projection displays for educational demonstrations, prototyping, and artistic installations without specialized equipment.